Silver (Ag) doped graphitic carbon nitride (g-C3N4)/biochar composite photocatalyst for improved photocatalytic degradation of ciprofloxacin (CIP) - Ijlal Idrees; Muhammad Zafar; Malik Adeel Umer; Fahad Rehman; Abdul Razzaq; Seongwan Kim; Yunsook Yang; Woo Young Kim (Results in Physics)
Dumping pharmaceutical wastewater into aquatic bodies vigorously adds to environmental pollution and amplifies antibiotic-resilient bacteria (ARB), a potential danger to humans and living organisms. Among several wastewater treatment methods, the photocatalysis approach under the umbrella of advanced oxidation processes (AOPs) offers a sustainable, inexpensive, and comprehensive treatment of emerging pharmaceutical pollutants (PEPs). Until today, amongst a variety of photocatalysts developed, graphitic carbon nitride, g-C3N4, (GCN), is considered a relatively low-cost, harmless, thermally stable, and to some extent visible light active (VLA) photocatalyst. Further, Biochar (BC) has emerged as an environmental friendly carbonaceous compound with good surface area, adsorption, and electrical conductivity. Hence being inspired by the characteristics of GCN and BC, a facile and captivating approach of composite photocatalysts comprising ternary components Ag, GCN, and BC is executed in the present work. The pivotal focal point is to enhance the optical absorption of GCN photocatalyst within visible light range by silver (Ag) doping strategy and boost the photogenerated charges separation by coupling with BC, both factors ultimately upsurging the photocatalytic performance. The photocatalytic performance of synthesized Ag-doped GCN/Biochar (ABCN) composite photocatalysts is assessed via the degradation of Ciprofloxacin (CIP) antibiotic, a common quinolone. The photocatalytic performance is optimized by varying the content of Ag dopant in the composite photocatalyst. The best sample 0.10-ABCN (with 10 wt% Ag content) exhibits the highest photocatalytic activity i.e. 70 % degradation of CIP (after 4 h of light irradiation), which is 3 times better than the pure GCN sample (25 %). Results from experimentation suggest that the strategy of composite photocatalyst fabrication based on the doping effect and fusing with carbonaceous material improved the photocatalytic efficiency mainly ascribed to improved optical absorbance and efficient charge separation.